Kesalahan dan Interferensi Bahasa Pada Buku Ajar Bahasa Arab Madrasah Tsanawiyah - Wafi, Hibatul; Hidayati, Nurfitria; Hakim, Faried Rochman; Muhajir, Muhajir (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
Mistakes will often be found in using Arabic both orally and in writing. This phenomenon is not uncommon. However, it has become commonplace due to the lack of ability of language users, especially Indonesian learners, to understand the structure of a second language, namely Arabic. Including elements of the first language into the second language has led to language deviations. Therefore, this study aims to examine errors and language interference found in Arabic textbooks for class VIII MTs (KEMENAG) in 2020. This research is qualitative research using error analysis methods. The data sources used are Arabic phrases and clauses, which have been identified based on the form of the error. The result of this study is that there are language errors in Arabic writing which are classified into several errors based on syntactic, phonological, morphological, and cultural aspects. Meanwhile, language interference was found based on morphological and cultural aspects.